Perbandingan Perbandingan Tingkat Kepatuhan Mengkonsumsi Multi Mikronutrien Suplemen (MMS) dan Tablet Tambah Darah (TTD) pada Ibu Hamil di Puskesmas Mulyorejo Surabaya: Perbandingan Tingkat Kepatuhan Mengonsumsi Multi Mikronutrien Suplemen dan Tablet Tambah Darah pada Ibu Hamil di Puskesmas Mulyorejo, Surabaya - Abidah, Nisrina; Sumarmi, Sri (Universitas Airlangga, 2024)
Background: The level of adherence is an indicator of the successful implementation of a program to provide both multiple micronutrient supplements (MMS) and iron folic acid (IFA). Moreover, factors that may have an impact on the level of adherence are knowledge level, consumption acceptability, characteristic acceptability, and family support. Objectives: To analyze the relationship and differences in the level of adherence of pregnant women to consuming MMS and IFA in the work area of Mulyorejo Public Health Center, Surabaya. Methods: This study is an observational study (prospective cohort design). A total of 244 samples from each of the two sample groups, which are the MMS group and the IFA group, were observed for 30 days. This study was expected to discover the adherence level of pregnant women to consuming MMS or IFA. In addition, the Mann-Whitney test was used in the comparative analysis, and the chi-square test was used in the relationship analysis. Results: According to the findings, it was discovered that pregnant women who consumed MMS had a higher average adherence rate (79.9%) compared to those who consumed IFA (71.2%). However, the results showed that there was no significant difference between the two (p-value = 0.400), and identical results applied for knowledge level, consumption acceptability, and characteristic acceptability. Moreover, in comparison to the IFA group (32.2), the MMS group had a higher average family support (34.9). Additionally, there was a relationship between the adherence level and both knowledge level and consumption acceptability (p-value<0,05), but there was no relationship between the adherence level and family support (p-value>0.05). Conclusions: There was no significant difference among the variables. In addition, there was a relationship between the adherence level and both knowledge level and consumption acceptability, but not between the adherence level and family support.